Ultrasonication-Assisted Synthesis of ZnxCd1−xS for Enhanced Visible-Light Photocatalytic Activity - Lei Yang (Catalysts, 2020)
ZnxCd1−xS as a solid solution photocatalyst has attracted widespread attention for its unique adjustable band gap structure and good and stable performance. A novel synthesis approach for ZnxCd1−xS is still required to further improve its performance. In this study, we synthesized a series of ZnxCd1−xS (x = 0−1) solid solutions via an ultrasonication-assisted hydrothermal route. In comparison with conventional methods of preparation, the sample prepared by our innovative method showed enhanced photocatalytic activity for the degradation of a methyl orange (MO) solution under visible light due to its high crystallinity and small crystallite size. Furthermore, the composition and bandgap of ZnxCd1−xS can be tuned by adjusting the mole ratio of Zn2+/Cd2+. Zn0.3Cd0.7S shows the highest level of activity and stability for the degradation of MO with k = 0.85 h−1, which is 2.2 times higher than that of CdS. The balance between band gap structure-directed redox capacity and light absorption of Zn0.3Cd0.7S accounts for its high photocatalytic performance, both of which are determined by the composition of the solid solution. Also, a degradation mechanism of MO over the sample is tentatively proposed. This study demonstrates a new strategy to synthesize highly efficient sulfide photocatalysts.